Meningkatkan keterampilan bermain taktis sepak bola melalui pendekatan model pembelajaran permainan taktis - Tono Nugraha (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2021)
The purpose of this action research is to determine the extent to which the tactical game learning model approach can improve the ability to execute skills, make decisions, support, in soccer game situations. The research subjects were students of Class XII IPS 3, Academic Year 2017/2018 totaling 43 people. The object of research is tactical playing skills. Data on tactical playing skills were collected using observation instruments. Skills assessment is quantitative data from observations which are then converted into qualitative data. The research data were analyzed descriptively qualitatively. This action research is said to be successful if it meets the following criteria: (a) the minimum score for the implementation of the learning process with the criteria